Use of Biomonitoring Tools to Detect Water Quality-Dependent Ecosystem (Macroinvertebrate) Responses in Lentic Systems: The Examples of Lakes İznik and Manyas, Türkiye - Mercan Deniz; Arslan Naime (Oceanological and Hydrobiological Studies)
Lakes İznik and Manyas located in Türkiye are important biodiversity resources in the Palearctic region. No studies to date have explored the ecological statuses of these lakes together with their water quality based on biotic indices utilizing benthic macroinvertebrates. In this study, some parameters listed in the SWQMR of Türkiye were measured to determine the ecological quality of the lakes. Biotic indices included in the WFD and bacteriological parameters in terms of human health were also evaluated for these lakes. Sampling was performed at 6 stations in 2018-2019. Results for the zoobenthic community structure indicate that Lake İznik has started to become organically polluted and Lake Manyas is more polluted. Also, the biological index results for Lake İznik also show that the lake water quality has started to decrease and that pollution conditions have occurred, pointing to class III water quality. It is clear that there is pollution pressure in Lake İznik. However, according to the results, the macrozoobenthic community structure, diversity, and water quality of Lake İznik seem to be better than those of Lake Manyas. According to the results of the water qualities in the lakes, precautions should be taken to eliminate the negative pressures seen in both lakes.